Effects of β2‐Adrenergic Agonists on Risk of Parkinson's Disease in COPD: A Population‐Based Study. Issue 5 (1st April 2020) - Chen, Wenjia; Sadatsafavi, Mohsen; Tavakoli, Hamid; Samii, Ali; Etminan, Mahyar
Abstract : Introduction: Multiple studies have investigated the role of β2 ‐adrenoreceptor agonists on the risk of Parkinson's disease (PD). However, whether β2 ‐agonist use is associated with the risk of PD in patients with chronic obstructive pulmonary disease (COPD) has not been examined to date. Objectives: To examine the association between use of β2 ‐agonist and the risk of PD in patients with COPD. Methods: A case‐control study nested within a cohort of patients with COPD using the British Columbia health administrative databases from 1997 to 2015 was performed. Among a cohort of patients with COPD, all cases of PD were identified, and matched each case to up to five controls by age and calendar time. The use of β2 ‐agonists was assessed between the third and fourth year preceding the date of PD diagnosis, followed by additional two years of grace period (between the first and second year preceding PD incidence) to control for PD latency. The use of β2 ‐agonists was categorized into three levels: regular use (≥ 1 dispensation for every 6 months), irregular use (dispensation in one to three 6‐month periods), and no use. A conditional logistic regression model was used to estimate the rate ratio of PD according to β2‐agonist use, rigorously controlling for confounding variables. Results: Among 242, 218 COPD patients, 732 PD cases and 3660 controls were identified. Use of β2 ‐agonists did not significantly affect the subsequent risk of PD ( vs no use, adjusted rate ratios: regular use, 1.14 [95% CI: 0.93, 1.40, p=0.21], irregular use, 1.15 [95% CI: 0.92, 1.45, p=0.22]). Results remained consistent with competing risk sensitivity analysis. Conclusion: Use of β2 ‐agonists does not appear to affect the risk of PD in a real‐world COPD population.